PERMASALAHAN SEKOLAH DI PERKOTAAN - M. Sabiqul Huda (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Education is the right of every citizen and is the noble aspiration of the Indonesian nation for the general welfare and the intellectual life of the nation as stated in the 1945 Constitution. However, in fact, there are still many imbalances in the world of education in Indonesia, including in urban areas. In general, the condition of schools in cities is more advanced than in villages. Judging from the facilities, schools in the city have sufficient facilities to support learning. In addition to good learning facilities, teachers in urban areas also have high competencies. However, it is unfortunate that many children drop out of school because school fees are quite expensive